Kantian Ontological Æsthetics: Of Shedding Light on Contemporary A.I. Art Controversies - Servana, Alvin (Con-Textos Kantianos. International Journal of Philosophy, 2026)
As artificial intelligence redefines everything, including creative production, the argument for a renewed necessity for grounding is ever more pronounced. In this paper, I take the Kantian transcendental æsthetics to be the clearest voice in addressing these controversies in contemporary arts. Drawing on Kant’s “Critique of Judgment”, I contend here that the universal validity claimed in æsthetic judgment, particularly evident in debates surrounding A.I.-generated art, cannot be adequately explained by any available alternatives. By critically analysing Kantian concepts: disinterestedness, universality, purposiveness without purpose, and subjective necessity, I demonstrate in this treatise that modern responses to A.I. art expose a deep-seated crisis in Æsthetic Theory—one that only the transcendental analysis can sufficiently address. The paper argues that Kantian Æsthetics provides the most coherent framework for understanding why A.I.-generated worx can evoke genuine æsthetic responses, whilst maintaining the normative standards necessary for critical discrimination. Positioned with the Analytic Method on Philosophy of Arts, I integrate in this endeavour rigorous conceptual analysis with contemporary æsthetic challenges to propose that Kant’s account of æsthetic judgment—properly understood in its subjective, yet universally valid character—lends the sturdiest foundation for addressing the ontological and epistemological questions raised by “artificial creativity”. I conclude this investigation by offering that fuller ontological grounding of æsthetic judgment may require extending Kantian transcendental philosophy towards the metaphysical commitments implicit in Kant’s own broader critical project.